2023
DOI: 10.2147/ijn.s418675
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials Modulating the Fate of Dental-Derived Mesenchymal Stem Cells Involved in Oral Tissue Reconstruction: A Systematic Review

Xingrui Li,
Yue Wang,
Denghao Huang
et al.

Abstract: The critical challenges in repairing oral soft and hard tissue defects are infection control and the recovery of functions. Compared to conventional tissue regeneration methods, nano-bioactive materials have become the optimal materials with excellent physicochemical properties and biocompatibility. Dental-derived mesenchymal stem cells (DMSCs) are a particular type of mesenchymal stromal cells (MSCs) with great potential in tissue regeneration and differentiation. This paper presents a review of the applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 211 publications
0
2
0
Order By: Relevance
“…TEM's high magnification and resolution capabilities enabled the visualization of the distribution of AuNPs within specific cellular compartments and that way proved the cellular uptake of 120 nm AuNPs within the cells. According to research, the cellular uptake of AuNPs, as well as their location and their lifespan inside the cell, plays a major role in their radiosensitizing effects and physical mechanisms of action [25]. Even though AuNPs did not seem to enter the nucleus, they were often located near the perinuclear region (Figure 3a,b).…”
Section: Assessment Of Distribution and Localization Of Aunps In Cell...mentioning
confidence: 99%
“…TEM's high magnification and resolution capabilities enabled the visualization of the distribution of AuNPs within specific cellular compartments and that way proved the cellular uptake of 120 nm AuNPs within the cells. According to research, the cellular uptake of AuNPs, as well as their location and their lifespan inside the cell, plays a major role in their radiosensitizing effects and physical mechanisms of action [25]. Even though AuNPs did not seem to enter the nucleus, they were often located near the perinuclear region (Figure 3a,b).…”
Section: Assessment Of Distribution and Localization Of Aunps In Cell...mentioning
confidence: 99%
“…The silver nanoparticles (AgNPs) were selected for the growth inhibition of resistant microorganisms including both Gram-positive and Gram-negative, however some reports suggested that these AgNPs can also inhibit the growth of fungi and viruses by disrupting the cell membrane and generating ROS [32].…”
Section: Selection Of Nanoparticlesmentioning
confidence: 99%